Mitochondria-targeted fluorescent thermometer monitors intracellular temperature gradient1. Issue 38 (11th May 2015) - Arai, Satoshi; Suzuki, Madoka; Park, Sung-Jin; Yoo, Jung Sun; Wang, Lu; Kang, Nam-Young; Ha, Hyung-Ho; Chang, Young-Tae
<x xml:space="preserve">Abstract</x> A small molecule fluorescent thermometer targeting mitochondria (Mito thermo yellow) enables us to monitor the intracellular temperature gradient, generated by exogenous heating in various cells.